In Situ Direct Laser Writing of 3D Graphene‐Laden Microstructures (Adv. Mater. Technol. 8/2021). Issue 8 (5th August 2021) - Restaino, Michael; Eckman, Noah; Alsharhan, Abdullah T.; Lamont, Andrew C.; Anderson, Jackson; Weinstein, Dana; Hall, Asha; Sochol, Ryan D.
Abstract : 3D Nanoprinting In article number 2100222, Ryan D. Sochol and colleagues introduce strategies for 3D nanoprinting graphene‐laden materials to enable the integration of geometrically sophisticated microelectronics with microfluidic systems. Fully 3D electrically conductive microstructures comprising reduced graphene oxide are additively manufactured directly inside of enclosed microchannels, offering a unique pathway to 3D microelectronics‐based microfluidic applications.